Purification and biochemical characterization of an extracellular serine peptidase from Aspergillus terreus - Biaggio, Rafael Tage; Silva, Ronivaldo Rodrigues da [UNESP]; Rosa, Nathalia Gonsales da; Ribeiro Leite, Rodrigo Simoes; Arantes, Eliane Candiani; Freitas Cabral, Tatiana Pereira de; Juliano, Maria A.; Juliano, Luiz; Cabral, Hamilton (Taylor & Francis Inc, 2016)
Peptidases are important because they play a central role in pharmaceutical, food, environmental, and other industrial processes. A serine peptidase from Aspergillus terreus was isolated after two chromatography steps that showed a yield of 15.5%. Its molecular mass was determined to be 43 kD, by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). This peptidase was active between pH 5.0 to 8.0 and had maximum activity at pH 7.0, at 45 degrees C. When exposited with 1 M of urea, the enzyme maintained 100% activity and used azocasein as substrate. The N-terminal (first 15 residues) showed 33% identity with the serine peptidase of Aspergillus clavatus ES1. The kinetics assays showed that subsite S-2 did not bind polar basic amino acids (His and Arg) nonpolar acidic amino acids (Asp and Glu). The subsite S-1 showed higher catalytic efficiency than the S-2 and S-3 subsites.
Keywords: Aspergillus; enzyme kinetics; filamentous fungi; N-terminal sequence; protease; protein